2008
DOI: 10.1107/s0108270108000127
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph of {2-[(2-hydroxyethyl)iminiomethyl]phenolato-κO}dioxido{2-[(2-oxidoethyl)iminomethyl]phenolato-κ3O,N,O′}molybdenum(VI)

Abstract: A second polymorphic form (form I) of the previously reported compound {2-[(2-hydroxyethyl)iminiomethyl]phenolato-kappaO}dioxido{2-[(2-oxidoethyl)iminomethyl]phenolato-kappa(3)O,N,O'}molybdenum(VI) (form II), [Mo(C(9)H(9)NO(2))O(2)(C(9)H(11)NO(2))], is presented. The title structure differs from the previously reported polymorph [Głowiak, Jerzykiewicz, Sobczak & Ziółkowski (2003). Inorg. Chim. Acta, 356, 387-392] by the fact that the asymmetric unit contains three molecules linked by O-H...O hydrogen bonds. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…With specific reference to the tridentate (O,N,O) ligands SAP and SAE, many stable MoO 2 L(D) compounds are known for both SAP (e.g. with D = MeOH, H 2 O, DMSO, amine, imidazoles, ethanol, SAEH 2 [7-10,12,14-16,19-21]) and SAE (D = DMF [22], MeOH [23,24], H 2 O [12], EtOH [13,25], SAEH 2 [8,26]). However, the SAE complexes show a greater tendency to dimerize, as indicated by the lower temperature for ethanol loss in the TGA [13].…”
Section: Dft Study: Relative Stability Of Moo 2 L(etoh) and [Moo 2 (Lmentioning
confidence: 99%
“…With specific reference to the tridentate (O,N,O) ligands SAP and SAE, many stable MoO 2 L(D) compounds are known for both SAP (e.g. with D = MeOH, H 2 O, DMSO, amine, imidazoles, ethanol, SAEH 2 [7-10,12,14-16,19-21]) and SAE (D = DMF [22], MeOH [23,24], H 2 O [12], EtOH [13,25], SAEH 2 [8,26]). However, the SAE complexes show a greater tendency to dimerize, as indicated by the lower temperature for ethanol loss in the TGA [13].…”
Section: Dft Study: Relative Stability Of Moo 2 L(etoh) and [Moo 2 (Lmentioning
confidence: 99%
“…Neutral dioxomolybdic complexes with ONO tridentate Schiff base ligands (L) seem good candidates. [21,32,[38][39][40][41][42][43] These complexes may exist in a dinuclear, oxo-bridged form [MoO2L]2 or as mononuclear octahedral adducts with a donor molecule D, [MoO2L(D)]. Several of these have been used as oxygen transfer agents or sulfoxidation catalysts, [21,[44][45][46][47][48][49][50] and also for epoxidation reactions in organic solvents, but only in the [MoO2L(D)] form.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to most other MoO2-based catalytic systems, which feature a (pseudo)octahedral coordination environment, where the oxidant TBHP may only add by proton transfer to an oxido [a] Mr. J. Morlot, Mr. N. Uyttebroeck, Dr. D. Agustin We have recently revisited the synthetic and coordination aspects of dioxomolybdenum complexes with the tridentate ONO ligands salicylideneaminophenol (H2SAP), salicylideneaminoethanol (H2SAE) and salicylideneaminomethylpropanol (H2SAMP), Scheme 1. [38][39] These ligands and the associated complexes are inexpensive and accessible by simple preparative procedures. We now describe the epoxidation activity of [MoO2L]2 complexes (L= SAP (5), SAE (6), SAMP (7)) and [MoO2(SAP)(MeOH)] (2) towards cis-cyclooctene using TBHP in water as oxidant without any added solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Two different ligands were synthesized using salicylaldehyde and 1,2 aminoethanol (leading to H2SAE ligand) or 1,2 aminophenol (leading to H2SAP ligand), Figure 2 [28]. Molecular structures of [MoO2(SAP)(EtOH)] and a polymorphic form of [MoO2(SAE)(SAEH2)] [29] were determined by X-ray diffraction. The "MoO2L" species have been studied in DFT according to the previously mentioned mechanism [26,27] and it was shown that both [MoO2(L)]2 (L = SAP, SAE) complexes needed less energy to be converted into the pentaco-ordinate mononuclear complex [MoO2L] than their ethanolstabilized congeners [MoO2L(EtOH)] [28].…”
Section: Preliminary Studies Toward the Best Backbone And Mechanistic...mentioning
confidence: 99%